Programme regional du CIAT l`amelioration du haricot dans la region des Grands Lacs en Afrique Centrale Rwanda/Zaire/Burundi. Rapport de stage 21.3.1987-8.4.1987 - Baltensweiler, M (International Center for Tropical Agriculture, 1987)
The geographical area involved in the CIAT Great Lakes bean project is described in detail, giving particular emphasis to Rwanda and the North and South Kivu subregions of Zaire. General information is also included on population, climate, and soils. Statistics on bean production, area planted, and no. of farmers growing this crop are presented for 1981-84 for each subregion. The differences between the data for both North and South Kivu are analyzed and discussed. (CIAT)